The relationship between intimate partner violence and maternal practices to correct child behavior: a study on women in Egypt - Dalal, Koustuv; Lawoko, Stephen; Jansson, Bjarne (Journal of injury and violence research, 2010)
This paper scrutinizes the association between maternal practices to correct child behavior and the mothers’ exposure to and attitudes towards intimate partner violence (IPV). Methods: Nationally representative data comprising 14 016 married women were retrieved from the Egyptian Demographic and Health Survey, 2005. Data on practices used to correct child behavior, exposure to IPV, attitudes towards IPV were our primary interest. Data were analyzed using Chi-square test and logistic regression. Results: The majority of the mothers reported use of violent methods, like shouting (90.6%), striking (69.1%) and slapping (39.3%) to correct child behavior. Seven percent of the mothers used only the explanation option. Exposure to physical IPV and tolerant attitudes towards IPV were associated with an augmented risk of using violent methods (shouting, striking or slapping) to correct child behavior. On the other hand non-tolerant attitudes towards IPV were associated with increased likelihood of sole use of the explanation method. Conclusions: We thus recommend the implementation of local parental education programs focusing on communicative skills to reduce IPV and related child abuse.
Keywords: Child abuse; Intimate partner violence; Attitudes; Mothers; Egypt